Vida de sacerdote. - Núñez Vargas, Benjamín 1915-1994; SEPSA (Heredia CR: UNA-IESTRA-GRECC, 1995)
Recoge algunos de los escritos más importantes del pensamiento social del Presbítero Benjamín Núñez.
Keywords: COSTA RICA; UNA; IGLESIA CATOLICA; NUÑEZ VARGAS, BENJAMIN